2017
DOI: 10.26480/icemi.01.2017.147.150
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of Customer Repeat Purchase Forecast on O2O platform

Abstract: On the O2O platform, accurate forecasting of customer repeat purchase is critical to the management of these businesses. Based on the NBD model and SMC model, and taking nearly thousands of different categories of businesses on the O2O platform "koubei" as study object, we implement empirical research on customer repeat purchase forecast. The main contents include: (1) the introductions about NBD and SMC model; (2) forecasting the customer repeat purchase of different categories of businesses based on the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Repeated purchase intention refers to the subjective probability/implied promise that an air traveler will continue to purchase a product from the same seller [1]. Traveler repeat purchase behavior has been a topic of interest in many contexts [22], such as in B2C e-commerce [1,10,23], on O2O platforms [24], in direct marketing [18,20], and in mobile commerce [8,25]. In our work, we focused on an airlines' direct marketing context, especially the low-cost carriers.…”
Section: Customer Repurchases and Purchase Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated purchase intention refers to the subjective probability/implied promise that an air traveler will continue to purchase a product from the same seller [1]. Traveler repeat purchase behavior has been a topic of interest in many contexts [22], such as in B2C e-commerce [1,10,23], on O2O platforms [24], in direct marketing [18,20], and in mobile commerce [8,25]. In our work, we focused on an airlines' direct marketing context, especially the low-cost carriers.…”
Section: Customer Repurchases and Purchase Intentionsmentioning
confidence: 99%
“…(3) SVM models represent a specific type of learning algorithm characterized by the capacity control of the decision function, the use of the kernel functions, and the sparsity of solutions [24]. Prior work has shown that SVMs [51] are excellent tools for predictive tasks.…”
Section: Framework Designmentioning
confidence: 99%